Rydberg Molecules Bound by Strong Light Fields - Simon Hollerith; Valentin Walther; Kritsana Srakaew; David Wei; Daniel Adler; Suchita Agrawal; Pascal Weckesser; Immanuel Bloch; Johannes Zeiher (PRX Quantum, 2024)
The coupling of an isolated quantum state to a continuum is typically associated with decoherence and decreased lifetime. For coupling rates larger than the bandwidth of the associated continuum, decoherence can be mitigated, and new stable eigenstates emerge. Here, we laser-couple diatomic molecules of highly excited Rydberg atoms, so-called Rydberg macrodimers, to a continuum of free motional states. Enabled by their small vibrational eigenfrequencies, we achieve the regime of strong continuum couplings and observe the appearance of new resonances. We explain the observed spectroscopic features as molecular states emerging in the presence of the light field using a Fano model. For atoms arranged on a lattice, we predict the strong continuum coupling to even stabilize triatomic molecules and find the first signatures of these by observing three-atom loss correlations using quantum gas microscopy. Our results present a mechanism to control decoherence and bind polyatomic molecules using strong light-matter interactions.